2020
DOI: 10.1002/adfm.202007294
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Cu‐Naphthalene‐Phosphonate Metal–Organic Framework with Ultra‐High Electrical Conductivity

Abstract: A conductive phosphonate metal-organic framework (MOF), [{Cu(H 2 O)} (2,6-NDPA) 0.5 ] (NDPA = naphthalenediphosphonic acid), which contains a 2D inorganic building unit (IBU) comprised of a continuous edge-sharing sheet of copper phosphonate polyhedra is reported. The 2D IBUs are connected to each other via polyaromatic 2,6-NDPA's, forming a 3D pillared-layered MOF structure. This MOF, known as TUB40, has a narrow band gap of 1.42 eV, a record high average electrical conductance of 2 × 10 2 S m −1 at room temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…In fact, we recently reported the highest single-crystal conductivity for a threedimensional MOF using arylphosphonic acid linkers. [37,53,54] Phosphonate MOFs possess extremely rich metal-binding modes compared to any other MOF family in the literature, which give rise to diverse IBUs in one and two dimensions. [55][56][57] Phosphonate MOFs with one-dimensional IBUs generally form one-dimensional void channels surrounded by well-stacked aromatic units, [58] while those with two-dimensional IBUs form pillared-layered networks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, we recently reported the highest single-crystal conductivity for a threedimensional MOF using arylphosphonic acid linkers. [37,53,54] Phosphonate MOFs possess extremely rich metal-binding modes compared to any other MOF family in the literature, which give rise to diverse IBUs in one and two dimensions. [55][56][57] Phosphonate MOFs with one-dimensional IBUs generally form one-dimensional void channels surrounded by well-stacked aromatic units, [58] while those with two-dimensional IBUs form pillared-layered networks.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the two‐dimensional conductive MOFs, we have recently shown that arylphosphonic acid linkers with molecular, one‐, and two‐dimensional IBUs can produce electrically conductive three‐dimensional MOFs via electron‐hopping and extended conjugation mechanisms. In fact, we recently reported the highest single‐crystal conductivity for a three‐dimensional MOF using arylphosphonic acid linkers [37,53,54] . Phosphonate MOFs possess extremely rich metal‐binding modes compared to any other MOF family in the literature, which give rise to diverse IBUs in one and two dimensions [55–57] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported the first highly stable semiconductive copper-phosphonate MOFs TUB75 and TUB40 with directionally dependent electrical conductivities in the 10 -3 and 10 3 S/m range. [33][34][35] In a related study, we reported the first semiconductive permanently microporous hydrogen-bonded phosphonic acid framework (constructed using the p-H 8 TPPA linker) with a band gap of 1.54 eV. 36 To the best of our knowledge, no semiconductive zincphosphonate MOFs have been reported in the literature.…”
Section: Semiconductive Phosphonate Mofsmentioning
confidence: 99%
“…In fact, we recently reported the highest single-crystal conductivity for a three-dimensional MOF using arylphosphonic acid linkers. 37,53,54 Phosphonate MOFs possess extremely rich metal-binding modes compared to any other MOF family in the literature, which give rise to diverse IBUs in one and two dimensions. [55][56][57] Phosphonate MOFs with one-dimensional IBUs generally form one-dimensional void channels surrounded by well-stacked aromatic units, 58 while those with two-dimensional IBUs form pillared-layered networks.…”
Section: Introductionmentioning
confidence: 99%
“…55 It is believed that the well-layered aromatic units in such phosphonate MOFs help promote electron hopping and that the continuous arrangement of M-O-P polyhedra in the IBUs extend the conjugation. 37,53 Moreover, due to their exceptionally high thermal and chemical stabilities, phosphonate MOFs could be suitable for applications such as electrodes in supercapacitors for electric vehicles and the storage/supply of energy produced by solar panels and wind turbines. 12,[59][60][61] In this work, we report the crystal structure of a newly synthesized phosphonate MOF, termed TUB1, which possesses a unique one-dimensional IBU composed of square planar and distorted trigonal bipyramidal copper(II) ions, and a tris-deprotonated methane tetra-pphenylphosphonic acid linker.…”
Section: Introductionmentioning
confidence: 99%